Le frontiere fatali del nazionalismo - Maria Russo (Phenomenology and Mind, 2015)
Ortega’s prophetic perspective locates the critical points in European international relations, the decadence of democracy and those contradictions ready to explode deriving from the naive post First World War pacifism. Ortega detects the appearance of the massified man as the symbol of moral degeneration of European people, pointing out the inadequacy of the intellectual social class in rule of the minority.